Dinamika Perilaku Agresif Klitih dan Peran Bimbingan Konseling dalam Upaya Preventif: Tinjauan Literatur - Setyaningrum, Dhiya Ayu; Hadi, Tsania Intan Mulia; Saraswati, Sekar Wilujeng; M, Muslikah; Mahfud, Ashari (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The phenomenon of klitih in Yogyakarta has become a worrying social issue, especially because of the involvement of adolescents in violent acts that are often carried out without clear motives. This article aims to examine the dynamics of aggressive behavior of klitih perpetrators and examine the strategic role of guidance and counseling in preventive efforts against this deviant behavior. The method used is a literature review of scientific articles, journals, and relevant books obtained through academic platforms. The results of the study indicate that aggressive behavior in adolescents, including klitih, can be minimized through a guidance and counseling approach that focuses on developing emotional regulation, self-control, and social skills. School counselors have an important role in designing preventive programs based on student needs, such as mindfulness training and conflict resolution simulations. Thus, guidance and counseling services become a key instrument in creating a safe, supportive educational environment that is able to shape adolescent character positively in order to prevent the emergence of aggressive behavior in the future.